2021
DOI: 10.1080/17441692.2020.1864753
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of tuberculosis detection and prevention studies in prisons

Abstract: Many studies have demonstrated that prisons are hotspots of tuberculosis disease and transmission. Despite this, it remains unclear which interventions are most effective at controlling tuberculosis in prisons. The objective of this study was to evaluate the study designs used to investigate tuberculosis control in prisons, and the efficacy of interventions undertaken. This systematic review included published studies which had the aim of reducing TB incidence or prevalence, or increasing the number of people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although many studies have demonstrated that prisons are hotspots of tuberculosis and transmission, it remains unclear which interventions are most effective at controlling tuberculosis in prisons. 24 Active case finding at CCF targets only inmates from high prevalence countries, thus explaining the high number of prisoners not tested in our study.…”
Section: To Offer Hepatitis B Immunizationmentioning
confidence: 80%
“…Although many studies have demonstrated that prisons are hotspots of tuberculosis and transmission, it remains unclear which interventions are most effective at controlling tuberculosis in prisons. 24 Active case finding at CCF targets only inmates from high prevalence countries, thus explaining the high number of prisoners not tested in our study.…”
Section: To Offer Hepatitis B Immunizationmentioning
confidence: 80%
“…One of the causes is the confinement context of overcrowding, where even the most elementary rules of preventive medicine cannot be enforced [ 29 ]. Other causes of the recurrence of the disease in prison include the high number of non-EU inmates, the high prevalence of HIV-positive inmates, the high incidence of substance abusers, and the lack of a suitable surveillance system [ 30 , 31 ]. By coughing, sneezing, or simply talking to each other, the bacteria enclosed in droplets are expelled into the closed environment of detention rooms and tend to float and remain in the air.…”
Section: Introductionmentioning
confidence: 99%
“…Some infectious diseases are more prevalent in prisons than in the general population. These include HIV infection, hepatitis and tuberculosis (Haeusler et al , 2021; Wali et al , 2019). Studies also report high proportions of non-communicable diseases in prisons, such as arterial hypertension, diabetes, mental illness (Bondolfi et al , 2020; Simeni Njonnou et al , 2020).…”
Section: Introductionmentioning
confidence: 99%